Improving the Performance of Administrative Employees in Madrasah Aliyah Negeri 1 Serang Regency - Nanang Fatchurochman (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to analyze the performance of administrative employees before strengthening efforts to improve the competence of administrative employees, increase competence and performance of administrative employees after increasing competence. This research method is a descriptive qualitative case study. Sources of data were obtained from observations and interviews, as many as six informants. The results of the study indicate that the organizational performance of Madrasah Aliyah Negeri 1 Serang Regency requires special attention, especially in terms of increasing its technical competence, as evidenced by the less than optimal way of solving it. Efforts made by schools in improving the performance of administrative employees by providing competency reinforcement. The success achieved in improving competence is marked by improved service, better response to consumer demand, working well and efficiently, and good communication between employees. After participating in the program, improving competence, the performance of administrative employees is assessed to improve through quality, quantity, timeliness, cost-effectiveness, need for supervision, and interpersonal input.